Flow cytometry aneuploidy and cell cycle indexing as a possible tool for differentiating between CD10+ diffuse large B‐cell lymphoma and follicular lymphoma. Issue 5 (9th December 2019) - Azoulay, David; Cohen, Hector I.; Dementiev, Eugene; Eshel, Elizabeth; Akria, Luiza; Shaoul, Ety; Horowitz, Netanel
Abstract: Background: Differential diagnosis between diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL) becomes a challenge when adequate biopsy is unavailable. The present study aimed to investigate the applicability of DNA cell cycle analysis by flow cytometry (FC) for differentiating between CD10 + DLBCL and FL. Methods: Data were collected from 57 specimens where CD5 − /CD10 + /light chain restricted B cells were detected. DNA staining was performed using the Coulter DNA Prep Kit. Cell cycle fractions were evaluated by automatic analysis using the ModFit LT software. Results: Histopathological analysis confirmed the diagnosis of CD10 + FL in 30 specimens (52.6%), CD10 + DLBCL in 24 specimens (42.1%), and CD10 + Burkitt lymphoma in 3 specimens (5.3%). A significantly higher rate of DNA aneuploidy was detected among CD10 + DLBCL than FL specimens (50 vs. 13.3% respectively, p = .003). Likewise, DNA index was significantly higher in CD10 + DLBCL relative to FL (1.26 ± 0.35 vs. 1.04 ± 0.16 respectively, p = .004). Notably, the proportion of cells in the S‐phase and proliferative fraction was significantly higher in CD10 + DLBCL than in CD10 + FL (S‐phase: 15.97 ± 13.94 vs. 4.43 ± 4.41 mean ± SD, respectively, p < .0001; proliferative fraction: 18.87 ± 15.17 vs. 5.78 ± 7.04 mean ± SD, respectively, p = .0001). Using a receiver operating characteristic analysis, optimal cutoffs for S‐phase ≥7% and proliferative fraction ≥9% were determined. These values could be used to differentiate between CD10 + DLBCL and CD10 + FL. Conclusion: Including DNA cell cycle analysis in the FC lymphoma assessment panel may be of diagnostic value in differentiating between CD10+ DLBCL and FL when adequate biopsy is unavailable.